On Inertial Relaxation CQ Algorithm for Split Feasibility Problems - Kesornprom, Suparat; Cholamjiak, Prasit (Communications in Mathematics and Applications, 2019)
In this work, we introduce an inertial relaxation CQ algorithm for the split feasibility problem in Hilbert spaces. We prove weak convergence theorem under suitable conditions. Numerical examples illustrating our methods’s efficiency are presented for comparing some known methods.